ANALISIS KINERJA KEUANGAN PERBANKAN DI INDONESIA SEBELUM DAN DIMASA PANDEMI COVID-19 - Maulina Dyah Permatasari; Erlina Widayanti Djatnicka; Adibah Yahya; Cici Suminar (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
The purpose of this study was to determine the condition of the soundness of the Bank based on the BUKU 4 category which was in very healthy, healthy or quite healthy conditions, as well as to compare the soundness level in 2018-2020, namely financial reports before and during the Covid 19 pandemic. Based on the CAMEL factor : Capital, Asset quality, Management, Earning and Liquidity Risk. The proxies used are Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Return on Assets (ROA), Return on Equity Ratio (ROE), Net Interest Margin (NIM), BOPO (Operating Expenditure to Operating Income), and Loanto Deposits Ratio (LDR). The population used in this study is a bank based on BUKU 4 category. The sampling technique used is purposive sampling method. The data analysis technique used is the Independent Sample T-test to compare the soundness of a Bank based on BUKU 4 categories as measured by financial performance using the Capital, Asset quality, Earning and Liquidity Risk approaches. The results of this study indicate that overall there are differences in the rating of the soundness of the Bank based on the BUKU 4 category, all Banks are in a